Education for Sustainable Development: A Solution to Reduce Food Insecurities in Liberia - Krubah Sisuse (Adult Education Research Conference, 2023)
The purpose of this study is to explore how Education for Sustainable Development integrated into the current curriculum can reduce food insecurity among college and university students in Liberia.
Keywords: Sustainable Development; food insecurity; curriculum